2023
DOI: 10.2339/politeknik.1002016
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anodic Coating on Fatigue Performance of AA7050-T7451 Alloy

Abstract: Önemli noktalar (Highlights) Anotlanmış ve anotlanmamış (ASM) numunelerin sertlik ve yüzey pürüzlülük değerleri / Hardness and surface roughness values of anodized and non-anodized (ASM) samples.  AA7050-T7451 alaşımının mekanik özellikleri üzerinde anodik oksidasyonun etkisi. / The effect of anodizing on mechanical properties of AA7050-T7451 alloy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Different types of electrolytes and anodizing processes are used according to the place of use of aluminum and the alloy type of aluminum used. Aluminum alloys are used in many different fields such as automotive and aerospace due to their superior properties [2,[6][7][8][9][10][11][12]. In addition to many superior properties (such as high corrosion resistance, light weight), weak tribological and interfacial mechanical properties also create some disadvantages [14].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of electrolytes and anodizing processes are used according to the place of use of aluminum and the alloy type of aluminum used. Aluminum alloys are used in many different fields such as automotive and aerospace due to their superior properties [2,[6][7][8][9][10][11][12]. In addition to many superior properties (such as high corrosion resistance, light weight), weak tribological and interfacial mechanical properties also create some disadvantages [14].…”
Section: Introductionmentioning
confidence: 99%
“…The fatigue life of the component has been obtained with the N-Code and physical tests. Akyildiz et al [28] experimentally investigated the effects of anodic coating on the fatigue strength of AA7050-T7451 alloy. S-N fatigue curves created with the help of the test data and Weibull equation showed that the anodic treatment significantly affected the fatigue performance of the alloy.…”
Section: Introductionmentioning
confidence: 99%